Effect of poly(ether–ether–sulfone) concentration on the morphology, performance, thermal stability, mechanical strength, and antifouling of asymmetric cellulose acetate ultrafiltration membranes. (September 2013) - Maheswari, P.; Mohan, D.
The aim of the present work is to investigate the morphology, performance, thermal stability, mechanical strength, and antifouling of the poly(ether–ether–sulfone) (PEES)-incorporated asymmetric cellulose acetate (CA)-blended ultrafiltration membranes. High-performance CA/PEES blend ultrafiltration membranes were prepared by the phase inversion technique. The effects of PEES concentration (0–30 wt%) on pure water permeability (PWP), water content, porosity, molecular weight cutoff, mean pore size, morphology, hydrophilicity, and thermal and mechanical properties of the CA/PEES blend membranes were investigated. Morphological studies were carried out using scanning electron microscopy. scanning electron microscopic studies revealed that the incorporation of PEES resulted in the formation of a thin top layer, a porous sub-layer, and the open pores in the bottom layer. The thermal properties of these polymeric membranes were evaluated by thermogravimetric and differential thermogravimetric analyses measurements, whereas the glass transition temperature of the membranes was calculated by differential scanning calorimetry. With the increase in the concentration of PEES on the CA membranes, the PWP, hydrophilicity, water content, porosity, the thermal stability, glass transition temperature, tensile strength, tensile modulus, and elongation at break significantly improved in the blend membranes. The efficiency of these membranes in the separation of commercially important proteins such as bovine serum albumin (BSA), egg albumin, pepsin, and trypsin was studied and found to be enhanced as compared to CA membranes. In fouling experiments, BSA was used as the model protein, and flux recovery ratio (FRR) of the membranes was calculated. Attempts have been made to correlate the changes in membrane morphology with pure water flux, water content, porosity, thermal and mechanical stability, separation efficiency, and antifouling property of the CA/PEES membranes. It has been demonstrated that the fouling-resistant ability of CA/PEES membranes is enhanced due to the high FRR with the addition of PEES in the casting solution. Based on the findings, it can be concluded that the membranes prepared with 80/20 composition of CA/PEES blend membranes are promising candidates for industrial applications.